Lafora’s disease in a free-ranging toco toucan (Ramphastos toco) with neurologic disease - Santana, Clarissa Helena; Oliveira, Ayisa Rodrigues; Souza, Lucas dos Reis de; Carvalho, Thaynara Parente de; Pereira, Fernanda Mara Aragão Macedo; Silva, Laice Alves da; Pimentel, Samantha Pinheiro; Santos, Daniel Oliveira dos; Soares-Neto, Lauro Leite; Courbilly, Andressa Quinalia; Silva, Jéssica Magalhães da; Paixão, Tatiane Alves da; et al. (Brazilian Journal of Veterinary Pathology, 2023)
Lafora’s disease is a genetic disease associated to mutations in genes that encodes laforin and malin, which results in intracellular polyglucan storage. The present report describes a case of Lafora’s disease in a toco toucan with episodes of incoordination and myoclonus that resulted in traumatic lesions and fracture of the left hindlimb. The bird was euthanized and submitted to necropsy. Microscopically there were abundant PAS-positive and diastasis-resistant Lafora’s inclusion bodies in neurons in the cerebellum, supporting the diagnosis of Lafora’s disease.